Prosthetic memory: Re-creating the experience of trauma in Iñárritu’s 11'09''01 - Shuri Mariasih Gietty Tambunan (EduLite: Journal of English Education, Literature and Culture, 2019)
9/11 will always be a traumatic experience not only for Americans but also for the rest of the world. This trauma has been re-articulated in a number of mass culture or popular culture products, such as novels or films. As argued by Landsberg (2004), mass culture could be used to attract the public in making sense of history, memory, politics and identity, including traumatic moments. In this article, the chosen case, a short film by Iñárritu’s entitled 11'09''01 shows how a cultural product intended for the masses has the potentials to change the structure of memory construction. The film has been criticized to be focusing on the traumatic aspect and do not highlight the heroic discourse, which was the most celebrated notion of the 9/11 tragedy. As the most experimental entry, this article argues that the short film among the others in the same project represents an effort to empathize with the pain felt on that day by utilizing ‘authentic’ materials, such as segments of media broadcasts from all over the world and recordings of the victims’ last phone calls to their loved ones. It also uses the images of people falling or jumping from the two towers leading into the ethical challenges for the cinematic documentation of a traumatic event, which will also be discussed in this article. The main method of analysis is textual analysis and Landsberg’s conceptualization of Prosthetic Memory is used to interpret the data. The article concludes that the short film could be seen as a Transferential Space in transferring memories of 9/11 to the audience who might not have experience it directly.